2014
DOI: 10.1038/nn.3691
|View full text |Cite
|
Sign up to set email alerts
|

Astrocyte Kir4.1 ion channel deficits contribute to neuronal dysfunction in Huntington's disease model mice

Abstract: Huntington's disease (HD) is characterized by striatal medium spiny neuron (MSN) dysfunction, but the underlying mechanisms remain unclear. We explored roles for astrocytes, which display mutant huntingtin in HD patients and mouse models. We found that symptom onset in R6/2 and Q175 HD mouse models is not associated with classical astrogliosis, but is associated with decreased Kir4.1 K+ channel functional expression, leading to elevated in vivo levels of striatal extracellular K+, which increased MSN excitabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
486
2
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 517 publications
(536 citation statements)
references
References 49 publications
26
486
2
4
Order By: Relevance
“…Reduced activity of the astrocyte potassium channel K ir 4.1 in HD mice was associated with increased extracellular potassium concentrations and a depolarized MSN membrane potential [69]. These data suggest that astrocytes might represent an important target for normalizing MSN function, in addition to the MSNs themselves.…”
Section: Msn Dysfunction In Hd Modelsmentioning
confidence: 80%
“…Reduced activity of the astrocyte potassium channel K ir 4.1 in HD mice was associated with increased extracellular potassium concentrations and a depolarized MSN membrane potential [69]. These data suggest that astrocytes might represent an important target for normalizing MSN function, in addition to the MSNs themselves.…”
Section: Msn Dysfunction In Hd Modelsmentioning
confidence: 80%
“…The control sample (GCM wt scrambled) shown in b and in Figure 3b is the same. See Supplementary Figure 9 for full-length pictures of the blots shown in b HD, 37 highlighting that some electrophysiological features of striatal dysfunction in HD can be secondary to glial disturbances. Here, we demonstrate that HD astrocytes affect neuronal function through their reduced synthesis and secretion of cholesterol bound to apoE lipoproteins.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased expression of Kir4.1 K + channels leads to elevated striatal extracellular K + in vivo which can result in depolarization of neurons. Genetic restoration of Kir4.1 levels in striatal astrocytes returned extracellular K + and MSN excitability to normal, along with improvement of some motor functions in R6/2 mice (Tong et al, 2014). Recent work confirmed that the loss of astrocytic Kir4.1‐ and EAAT2‐mediated homeostatic functions in R6/2 mice compromises glutamate handling and Ca 2+ signaling, contributing to MSNs pathology in the striatum (Jiang, Diaz‐Castro, Looger, & Khakh, 2016).…”
Section: Astrocytes In the Diseased Brain Are Central To Neuropathologymentioning
confidence: 99%